1968
DOI: 10.3758/bf03331158
|View full text |Cite
|
Sign up to set email alerts
|

A circadian variable in self-exposure to light by the rat

Abstract: Determinations of illuminance preference of rats have been made by Lockard (1962Lockard ( , 1963 and by Johnson (1%4, 1965). Using bar pressing and locomotor response measures respectively, data obtained by these investigators differ in support of a preference hypothesis (Lockard & Lockard, 1964) suggesting a range of dim illuminations which have greater preference value than darkness. A confounding issue is the reinforcement value of stimulus change which, as Johnson (1965, p. 541) noted, varies in specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1970
1970
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…periodicities have ,. been limited to one rat subject (Thor & Hoats, 1968), ;our results; are included here. Most subjects exhibited circadian onsets of activity , similar , to those expected from nocturnal, animals kept in constant darkness (Aschoff, 1965), i.e., day length shorter than 24 hr.…”
Section: Discussionmentioning
confidence: 99%
“…periodicities have ,. been limited to one rat subject (Thor & Hoats, 1968), ;our results; are included here. Most subjects exhibited circadian onsets of activity , similar , to those expected from nocturnal, animals kept in constant darkness (Aschoff, 1965), i.e., day length shorter than 24 hr.…”
Section: Discussionmentioning
confidence: 99%
“…However, contemporary life is not merely subject to the daily rhythms of nature; we can alter our environment to match our internal state, creating a reciprocal loop between the environment and bodily rhythms. The mutual entrainment of these different rhythms may generate a new emergent circadian rhythm 7,8 that could alter our behavior and cognition. However, few studies have identi ed such emergent rhythms and evaluated their behavioral, physiological, and cognitive effects.…”
Section: Introductionmentioning
confidence: 99%
“…From the limited evidence available, Kish (1966) concluded that the most parsimonious way of viewing sensory reinforcement behavior was in terms of "a single 'stimulus hunger' or drive for stimulation rather than a series of drives specific to different test situations, or sensory modalities, or perhaps both [p. 127] ." Others have also postulated a single general need for stimulus change in accounting for sensory reinforcement (e.g., Isaac, 1962;Frieman, 1967; Thor & Hoats, 1968). The basis for this need is often in terms of a parallel between the sensory deprivation studies (e.g., Brownfield, 1965) and the research on curiosity-exploratory behavior, with both phenomena seen as stemming from a general need for exteroceptive stimulus change (e.g., Jones, 1966;Riesen, 1966;Schultz, 1965Schultz, , 1967.…”
mentioning
confidence: 99%